2015
DOI: 10.1016/j.scr.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of human adult olfactory sphere cells as a cell source of neural progenitors

Abstract: Olfactory stem cells are generated from olfactory mucosa. Various culture conditions generate olfactory stem cells that differ according to species and developmental stage and have different progenitor or stem cell characteristics. Olfactory spheres (OSs) are clusters of progenitor or stem cells generated from olfactory mucosa in suspension culture. In this study, adult human OSs were generated and their characteristics analyzed. Human OSs were adequately produced from olfactory mucosa with area over 40 mm(2).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…The olfactory mucosa has multipotent horizontal basal cells that differentiate into olfactory sensory neurons during normal neuronal turnover as well as during tissue regeneration after injury . To date, several studies have described different techniques that olfactory stem cells are generated from olfactory mucosa, using various culture conditions according to the species or the presence of serum . However, the culture methods and cellular identity of olfactory stem cells have not been settled.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The olfactory mucosa has multipotent horizontal basal cells that differentiate into olfactory sensory neurons during normal neuronal turnover as well as during tissue regeneration after injury . To date, several studies have described different techniques that olfactory stem cells are generated from olfactory mucosa, using various culture conditions according to the species or the presence of serum . However, the culture methods and cellular identity of olfactory stem cells have not been settled.…”
Section: Discussionmentioning
confidence: 99%
“…However, the culture methods and cellular identity of olfactory stem cells have not been settled. Among those, some studies demonstrated that olfactory mucosa generated neurospheres that were multipotent in vitro and human olfactory neurospheres gave rise to neurons and glia, and self‐replicating . OSCs are a kind of cluster for stem cells generated from olfactory mucosa in suspension culture, and these cells express markers of neural stem cells, glial cells, neurons and mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, culture techniques have been established for human OE to generate populations of mitotically active neural progenitors that form neurospheres [28, 29, 31]. The resulting olfactory neurospheres and their derived cells are multipotent and capable of self-renewal, and can be differentiated into neurons and glia [29, 32].…”
Section: Oe-derived Tissue/cell Modelsmentioning
confidence: 99%
“…Indeed, olfactory lamina propria stem cells share membrane markers with bone marrow stem cells, and are named, olfactory ectomesenchymal stem cells [37]. Other groups have demonstrated that neurosphere-forming cells derived from the OE can be directed toward neuronal lineage restriction by sonic hedgehog, forskolin, and retinoic acid [38], and that human olfactory spheres express oligodendrocyte progenitor cell markers [31]. …”
Section: Oe-derived Tissue/cell Modelsmentioning
confidence: 99%